2020
DOI: 10.3390/nu12092769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Omega-3 Polyunsaturated Fatty Acid Supplementation on Non-Alcoholic Fatty Liver: A Systematic Review and Meta-Analysis

Abstract: (1) Aim: Non-alcoholic fatty liver disease (NAFLD) is a prevalent disease worldwide. Omega-3 polyunsaturated fatty acids (n-3 PUFAs) bear anti-inflammatory action and can ameliorate hyperlipidemia. We wish to appraise the effects of n-3 PUFAs supplement on NAFLD. (2) Methods: We searched CENTRAL, Embase, and MEDLINE on 29 March 2020 for randomized control trials (RCTs) on the effects of n-3 PUFAs supplementation in treating NAFLD. The Cochrane Collaboration’s tool was used to assess the risk of bias of include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 69 publications
(92 reference statements)
3
66
1
3
Order By: Relevance
“…In fact, many systematic reviews and meta-analyses of randomised controlled trials have addressed the topic of Omega-3 supplementation and its effect on patients suffering from NAFLD. These studies conclude that Omega 3 PUFAs supplementation (>3 g/day) is useful for the reduction of liver fat, hepatic enzymes, BMI, triglycerides, and cholesterol [ 115 , 116 ]. This potentially sets Omega-3 food supplementation as a safe, viable, and effective intervention to help treat NAFLD.…”
Section: Nutrition and Nafldmentioning
confidence: 99%
“…In fact, many systematic reviews and meta-analyses of randomised controlled trials have addressed the topic of Omega-3 supplementation and its effect on patients suffering from NAFLD. These studies conclude that Omega 3 PUFAs supplementation (>3 g/day) is useful for the reduction of liver fat, hepatic enzymes, BMI, triglycerides, and cholesterol [ 115 , 116 ]. This potentially sets Omega-3 food supplementation as a safe, viable, and effective intervention to help treat NAFLD.…”
Section: Nutrition and Nafldmentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acids (n-3 PUFAs) contain several long chain fatty acids, such as α-linolenic acid (α-ALA), stearidonic acid (SDA), eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) [ 115 ]. EPA and DHA decrease the levels of triglyceride and very-low-density lipoproteins, which are converted to low-density lipoprotein and intermediate-density lipoprotein [ 115 ]. Accumulating evidence also suggests that dietary n −3 PUFAs could improve insulin resistance by regulating mitochondrial function and mediating anti-inflammatory effects [ 115 ].…”
Section: Introductionmentioning
confidence: 99%
“…EPA and DHA decrease the levels of triglyceride and very-low-density lipoproteins, which are converted to low-density lipoprotein and intermediate-density lipoprotein [ 115 ]. Accumulating evidence also suggests that dietary n −3 PUFAs could improve insulin resistance by regulating mitochondrial function and mediating anti-inflammatory effects [ 115 ]. Several preclinical studies using animal NASH models have suggested that the supplementation of n −3 PUFAs could exert a positive impact on NAFLD by diminishing hepatic fat deposition and preventing the proinflammatory state [ 116 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study suggested that omega-3 fatty acids, a group of polyunsaturated fatty acids (PUFAs), have a positive effect in the treatment of different renal diseases such as diabetic nephropathy and cyclosporine nephrotoxicity [20]. In patients with NAFLD, studies showed that omega-3 may help in decrease liver fat, improving fatty liver and may also improve blood lipid levels and obesity [21]. Moreover, eicosapentaenoic acid (EPA) supplementation enhanced the cognitive function and was superior to docosahexaenoic acid (DHA) [22].…”
Section: Introductionmentioning
confidence: 99%